MENINGKATKAN HASIL BELAJAR EKONOMI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) - Desi Budiono; Ningrum Ningrum (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
The learning outcomes of class XI high school students are still low. In an effort to improve economic learning outcomes, the researcher intends to use a cooperative learning model of the Student Team Achievement Divisions (STAD) type. This learning model is used with the aim of helping economic education teachers in an effort to improve student economic learning outcomes. This study aims to determine the effect of the use of the Student Team Achievement Divisions (STAD) Cooperative Learning Model on the Economics Learning Outcomes of Class XI Social Sciences Students. The population in this study were students of class XI IPS SMA, which amounted to 63 students and consisted of 3 classes. The sample of this study amounted to 41 students which was carried out in 21 students of class XI IPS1 as the experimental class, and XI IPS2 as the control class which was determined by purposive sampling. To determine the level of validity and reliability, the K-R formula is used. 20: r_11=(k/(k-1))Ã—((V_t pq)/Vt) and to test the hypothesis, the Simple Linear Regression formula is used, namely = a + bx. The value of =36.0217+0.6594X followed by the t-count formula, namely t_hit= b/S_b = 6.81 and t_table = 1.73 with a significant level of 5% and t_table = 2.54 with a significant level of 1%. That way thit > ttab are 6.81 > 1.73 and 6.81 > 2.54.Keywords: Cooperative Learning Model, Student Team Achievement Divisions (STAD), Learning Outcomes, Economics.